Stereoselective hydrodehalogenation via a radical-based mechanism involving t-shaped chiral nickel(I) pincer complexes - Rettenmeier, Christoph Alexander; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2014)
Abstract We herein report the catalytic enantioselective hydrodehalogenation based on the interplay of a chiral molecular nickel(I)/nickel(II)hydride system. Prochiral geminal dihalogenides are dehalogenated via a secondary configurationally unstable, potentially metal-stabilized radical intermediate. In a subsequent step, the liberated radical is then trapped by the nickel(II) hydrido complex, present in a large excess under the catalytic conditions, which in turn induces the enantioselectivity during the hydrogen atom transfer onto the radical intermediate. These new chiral nickel(I) complexes were found to catalyze the asymmetric hydrodehalogenation of geminal dihalogenides with moderate to good enantiomeric excess values using LiEt3BH as reductant. The main side product generally observed is the dehalogenated alkene, whereas the hydrodehalogenation of the chiral monohalogen compound occurred much more slowly despite the large excess of reductant.
Gesehen am 30.07.2020